Nitrous oxide dataset for East Qinghai-Tibet Plateau waterways - Liwei Zhang; Xinghui Xia; Tom J Battin; Emily H Stanley (Environmental Data Initiative, 2021)
This dataset is a collation of 3-year direct measurement values of N 2 O concentrations and fluxes for East Qinghai-Tibet Plateau (EQTP) streams and rivers, along with information on location, hydrological, physical, and chemical conditions of the study sites. Given the rarity and high value of this EQTP data set, it will be very valuable for the next update to global riverine N 2 O flux estimates.